Relationship between Body Mass Index (BMI) and Disability Level of Low Back Pain (LBP) Patients - Ice Septriani Saragih; Maria Pujiastuti Simbolon; Reri Noor Amelia (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2025)
LBP (Low Back Pain) is a pain in the back, especially in the lower part, which is one of the main reasons for visiting healthcare facilities. Various risk factors have been identified as causes of LBP and disability in LBP patients, one of which is Body Mass Index (BMI). Although several studies have shown that BMI can worsen low back pain, the direct relationship between BMI and the level of disability experienced by patients remains inconsistent and inconclusive. The purpose of this study was to determine the relationship between BMI and disability in LBP patients. This type of research was quantitative research with a correlational design. The number of samples in this study was 38 people. The inclusion criteria for the sample in this study were patients with LBP who are still cooperative, fully conscious, and willing to participate as research respondents. The instrument used to measure disability was the Oswestry Disability Index (ODI) or the Oswestry Low Back Pain Disability Questionnaire, while Body Mass Index (BMI) was measured using the results of weight and height measurements. Data analysis was carried out using computerization to compile the frequency distribution and percentage of each variable, as well as using the the Sperman rank test to determine the relationship between variables. The results showed that 55.26% of respondents had ideal body weight and 55.26% of respondents had moderate disabilities. There is no relationship between BMI and disability in LBP patients. This study recommends research related to interventions that can reduce disability in LBP patients.